1993
DOI: 10.4319/lo.1993.38.5.0986
|View full text |Cite
|
Sign up to set email alerts
|

Predator‐induced phenotypic plasticity in Daphnia pulex: Life history and morphological responses to Notonecta and Chaoborus

Abstract: Results from a laboratory life-table study show Daphnia pulex has a unique set of rapidly induced responses to waterborne chemicals from each of two predator species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
2
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 28 publications
(64 reference statements)
6
65
2
3
Order By: Relevance
“…Daphnia, for example, exhibit a variety of responses (changes in morphology, life history traits, and DVM behaviour) when they are exposed to predators' kairomones, and Daphnia that occur in environments with abundant predators tend to be more sensitive to kairomones than those in environments with fewer predators (Parejko & Dodson 1991;Lüning 1992;Spitze 1992;Black 1993;De Meester 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Daphnia, for example, exhibit a variety of responses (changes in morphology, life history traits, and DVM behaviour) when they are exposed to predators' kairomones, and Daphnia that occur in environments with abundant predators tend to be more sensitive to kairomones than those in environments with fewer predators (Parejko & Dodson 1991;Lüning 1992;Spitze 1992;Black 1993;De Meester 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These processes may be well understood according to the classic Lotka-Volterra predator-prey function. Besides it has recently been demonstrated that predation pressure induces or stimulates physiological changes related to reproduction in numerous species of invertebrates (Stibor, 1992;Black, 1993;Lampert et al, 1994;Reimer, 1999). Thus predation should be viewed as a process of co-existence and co-evolution rather than as a strategy for the control or reduction of prey.…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic invertebrates have been shown to respond to chemicals released by their predators (Dodson 1989b). The response of prey to chemicals released by predators include induction of morphological defenses (Have1 1987;Dodson 1989a;Black 1993), change in life-history characteristics (Stibor 1992;Black 1993), and altered behavior (Dodson 1988a;Tjossem 1990). Although Tjossem (1990) and Dawidowicz (1990) showed that the vertical migration of Chaoborus flavicans is induced by the presence of fish chemicals, studies are still lacking that specify the presence of chemicals as a key factor that influences the behavior of Chaoborus.…”
mentioning
confidence: 99%
“…It is widely known that chemical cues from predators can alter structures (Black 1993) life-history characteristics (Stibor 1992), and behavior of the prey (Dodson 1988b). However, few studies have shown chemical cues from prey having similar effects on the predator.…”
mentioning
confidence: 99%